PROSPECTS OF IN VITRO CONSERVATION OF DATE PALM GENETIC DIVERSITY FORSUSTAINABLE PRODUCTION - Jain, S. Mohan (Emirates Journal of Food and Agriculture, 2011)
Plant genetic diversity is highly essential for the genetic improvement of crops for sustainable agriculture and its gradual loss is as a consequence to rapid human population growth, industrialization, deforestation, and natural calamities. In the future, the impact of climate change may have an adverse impact on sustainable date palm productions as well other crops. The conservation, distribution and proper utilization of plant genetic diversity/resources become necessary for the development and improvement of date palm cultivars for sustainable crop production. The conservation, distribution, and utilization of natural and induced genetic diversity have become essential by the establishment of gene/germplasm bank both at the national and international levels. The Gene bank should encourage researchers to survey and monitor the genetic diversity of natural populations and landraces on farmer's fields. In vitro conservation techniques, cryopreservation or cryo-storage and cold storage, are excellent system for genetic resources conservation of forest trees and horticultural crops. Cold-storage approach has disadvantage of frequent subculture and that may run into a risk of contamination and somaclonal variation. Cryo-storage has an advantage of long-term storage without going through frequent subcultures and somaclonal variation. For this, in vitro cultures are suitable, e.g. somatic embryos/ cell suspension, callus, and should be able to regenerate plants with minimal somaclonal variation. In date palm, the most common in vitro culture approach has been somatic embryogenesis, which is very much dependent on genotype and culture medium for plant multiplication, even though there is a risk of genetic variability among regenerated plants For the first time, cryo-storage of date palm somatic embryos was done in Tunisia, FAO/IAEA project, and plant regeneration is yet to be accomplished. In Asia, National Bureau of Plant Genetic Resources (NBPGRI, India) is the biggest germplasm bank, and conserves mainly local germplasm seed and vegetative propagated crops and introduces new crops as well.